1991
DOI: 10.1115/1.2910610
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Developing Free Convection Between Isothermal Vertical Plates

Abstract: Steady two-dimensional laminar free convection between isothermal vertical plates including entrance flow effects has been numerically investigated. The full elliptic forms of the Navier-Stokes and energy equations are solved using novel inlet flow boundary conditions. Results are presented for Prandtl number Pr = 0.7, Grashof number range 50 ≤ Grb ≤ 5×104, and channel aspect ratios of L/b = 10, 17, 24. New phenomena, such as inlet flow separation, have been observed. The results cast doubt on the validity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 0 publications
4
41
0
Order By: Relevance
“…The present results for the local Nusselt number are in better agreement with the experimental ones as shown in Figure 3(a). A comparison of the average Nusselt number (Nu) with experimental results by Elenbaas [1] and numerical results by Naylor et al [7] for di erent Rayleigh number is shown in Figure 3(b) and Table I. Good agreement between the present results and similar ones reported in the literature is indicated by Figure 3(b).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The present results for the local Nusselt number are in better agreement with the experimental ones as shown in Figure 3(a). A comparison of the average Nusselt number (Nu) with experimental results by Elenbaas [1] and numerical results by Naylor et al [7] for di erent Rayleigh number is shown in Figure 3(b) and Table I. Good agreement between the present results and similar ones reported in the literature is indicated by Figure 3(b).…”
Section: Resultssupporting
confidence: 90%
“…These calculations included the in uence of mesh sizes of 25 × 100, 50 × 100, 50 × 200 and 100 × 300 on the mean vertical velocity at section y=L = 0:77. The results of these calculations are shown in Figure 2 [6] and similar numerical results by Naylor et al [7]. The comparison is for the same Rayleigh number (3.11) and aspect ratio (L=b = 24).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Naylor et al [37] solved the full elliptic forms of the governing equations for pure natural convection using inlet flow boundary conditions based on the Jeffrey-Hamel flow in order to represent more realistically the entrance flow. Their solutions validated the inlet pressure approximation (p = −ρ 0 w 2 /2) commonly used in parabolic formulations.…”
Section: Channel Extensionsmentioning
confidence: 99%
“…The shapes of the walls at the entrance region, with sharp angles or smooth rounded surfaces, affect also significantly the fluid flows and heat transfer. Using entrance walls with right angles, Naylor et al [11] predicted a fluid separation at the channel inlet which is approximately correlated with the dimensional flow rate. Their inlet boundary conditions were based on JeffreyHamel flow which consists in a similarity solution of isothermal flow caused by the presence of a source or sink at the point of intersection of two walls.…”
mentioning
confidence: 99%